Caracterização de prováveis mecanismos de ação de derivados sintéticos heterocíclicos e precursores em modelo de tumores sólidos e leucemias. - Tulio Resende Freitas (2023)
Cancer currently ranks as the second-leading cause of death on a global scale. In general, existing oncological treatments entail frequent undesirable side effects and demonstrate limited efficacy. Heterocyclic compounds, constituting a fundamental structural unit in many marketed drugs, play a well-established and prominent role as antitumoral agents. In this context, this study aimed to assess, through in vitro experimentation and computational approaches, the cytotoxic action, apoptosis-inducing capacity, alterations in the cell cycle and gene expression, as well as possible molecular interactions of twenty-three (23) new heterocyclic compounds and precursors against cell lines associated with breast cancer (MDA-MB-231), ovarian cancer (TOV-21G), acute myeloid leukemia (THP-1), acute promyelocytic leukemia (HL-60), and chronic myeloid leukemia (K-562). To achieve this objective, cytotoxicity assays, flow cytometry analyses, gene expression evaluation, oral bioavailability study, and molecular modeling were employed. Among the compounds analyzed, GSCB76, GSCB82, and GSCB85 were found to be the most potent and selective, exhibiting considerably increased cytotoxicity [1,18 μM < IC50 < 7,66 μM] and targeted selectivity toward the MDA-MB-231 and THP-1 cell lines. Investigation into apoptosis induction and cell cycle alterations revealed that compounds GSCB76, GSCB82, and GSCB85 primarily promoted an increase in apoptotic THP-1 cells after 48 hours of treatment, while GSCB76 and GSCB82 induced cell cycle arrest in the G0/G1 phases in this same cell line. In terms of gene expression, a modification in the profile of genes involved in potential resistance and apoptosis mechanisms was observed. Furthermore, in silico analysis revealed that the three most active compounds have the potential to interact with Histone Deacetylase 8 (HDAC8), a target already associated with cancer, and also exhibit a high drug-like potential, suggesting the prospect of developing prototypes that can be administered orally. These results strengthen the potential use of these compounds as part of the search for new therapeutic approaches in the field of oncology.